Implementation of Law No. 32 of 2009 on Environmental Protection and Management of Medical Waste Post-COVID-19 in Public Health Centers of Medan City - Daulay, Amalia Dwi Azzahra; Syahrin, Alvi; Suhaidi, Suhaidi; Affila, Affila (Universitas Islam Negeri Sumatera Utara, 2025)
This study examines the implementation of Law No. 32 of 2009 on Environmental Protection and Management concerning post-COVID-19 medical waste in public health centers (Puskesmas) in Medan City. Hazardous and toxic (B3) medical waste increased during the pandemic and continues to pose environmental threats. As primary healthcare facilities, Puskesmas generate medical waste that must be properly managed, as noncompliance can negatively impact public health and the environment. This study aims to analyze the implementation of Law No. 32/2009, identify obstacles in managing post-COVID-19 medical waste, and evaluate the role of local governments in supervision. The research uses a normative legal method with a regulatory approach, supported by empirical data from interviews with relevant institutions, and employs policy implementation theory, legal system theory, and authority theory. Results indicate that medical waste management in Medan’s Puskesmas is not fully compliant with Law No. 32/2009 or its derivatives, such as Government Regulation No. 22/2021 and Ministry of Health Regulation No. 2/2023. Key challenges include limited B3 waste storage, constrained waste transportation budgets, and low public awareness. Recommendations include strengthening inter-agency coordination, enhancing Puskesmas waste management capacity, and stricter supervision and law enforcement to ensure sustainable environmental protection.